The EU Green Deal and its Implementation - Trüe, Christiane; Scholz, Lydia (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Climate change mitigation and the Green Deal will remain a central topic for the EU. As a major historical contributor to greenhouse gases, it has the opportunity to reverse this trend of ever more emissions, including by providing a model to leapfrog the carbon age: EU funding and the assessment of state aid and competition law; legal Instruments, including technical standardisation, criminal law sanctions and market-based measures, such as tax incentives or the future extension of emissions trading to consumers; education; the external dimension, a potential new green hegemony and the CBAM; social aspects; climate rights enforcement; and issues arising in specific sectors, including energy, transport, public procurement, urban planning and migration. With contributions by Līga Briķena | Walter Frenz | Lisa-Marie Hartwig | Trygve Ben Holland | Sarah Holland-Kunkel | Kirk W. Junker | María Luisa Jiménez Gómez | Marvin Jürgens | Mirko Kruse | Tatjana Muravska | Hans-Martin Niemeier |Kleoniki Pouikli | André Röhl | Lydia Scholz | Zynep Şentürk | Celia Maria Silva Carvalho | Marc Stauch | Sergejs Stacenko | Kai Stührenberg | Christiane Trüe | Jan Wedemeier